Adam i Maryla : dzieje romantycznej milosci Adama Mickiewicza i Maryli Wereszczakowny - Wawrzykowska-Wierciochowa, Dioniza (Warszawa : Instytut Wydawniczy Zwiazkow Zawodowych, 1990)
The biography and the love interest of Mickiewicz and Maryla.
Includes bibliographical references (p. [290]-297).
Keywords: Mickiewicz, Adam, -- 1798-1855 -- Relations with women; Wereszczakowna, Maryla, -- 1799-1863.; Poets, Polish -- 19th century -- Biography